The Paulo Freire's Critical Education Through the Teachings of Saminism in the Digital Era - Diaz Kusuma Atmaja (Amal Insani Foundation, 2024)
Looking at digitalisation events in Indonesia, this article formulates the problem of Paulo Freire's critical educational strategy in reconstructing Saminism culture regarding moral values. This research aims to analyse the development of Saminism culture in Blora Regency against the background of Saminism society and rapid educational growth. The Samin or Sikep community tends to maintain the teachings of Saminism in this digital era. Moreover, previously digitalisation was opposed by Saminis ideology as part of the principles of life of the Sikep community. Based on Paulo Freire's critical educational perspective and Samin Soerosentiko's Saminist teachings, researchers identified three important findings. First, the process of cultivating Saminism teachings through the Sikep family in the digital era. Second, the Sikep family is also the climax of critical education which contains elements of the codification of Saminism and contains acts of cognition. Three, the process of cultivating the teachings of Saminism is a step that contains critical educational elements.